Awareness and adoption strategies for improved agricultural practices (IAPs) by smallholder farmers in the Mbeya Region, Tanzania - Phenson Justine; Ádám Csorba; Caleb Melenya Ocansey; Brian Rotich; Isaiah Maket; Azaria Stephano Lameck; Mustapha Abdulkadir; Mohammed Ahmed MohammedZein; Erika Michéli; Yuri Andrei Gelsleichter (Discover Sustainability, 2025)
Abstract Although numerous studies have reported an increased yield upon adoption to improved agricultural practices (IAPs), yet smallholder farmers face limited access to this information. The objective of this study was to assess smallholder farmers' awareness and adoption of IAPs. A total of 206 active and registered households were surveyed by mixed sampling in the Mbeya region. The data was collected from smallholder farmers using the ODK collect tool through a well-structured questionnaire. The probit model and One-way ANOVA test were performed to identify predictor variables. Results pointed out that farming period, top dressing, flood exposure, fallowing time, soil information on IAPs, and knowledge about soil type showed a significant difference (p < 0.05) on the farmers’ adoption of IAPs. Moreover, 81% and 72% of the smallholder farmers surveyed showed a lack of awareness regarding the specific soil type and general soil information related to their farmland, respectively. Only 24% of farmers relied on agricultural experts (extension service officers) to get information on IAPs whereas 65% of the respondents were unfamiliar with neither Agricultural Extension Officers, non-governmental organizations (NGOs), Tanzania Agricultural Research Institute (TARI), nor Researchers from Higher Learning Institution (RHLI). About 59% of the female-headed households were found to have a better soil information on IAPs than men at a 5% significant level. Age and education level do not affect farmers’ adoption of IAPs with 72.5% of respondents motivated to adopt various IAPs in the surveyed area. This study highlights the need to highly consider agricultural extension officers as important agents in linking smallholder farmers with NGOs programs, agricultural research findings, and government programs to improve their livelihood. Graphical abstract